Retropharyngeal and lateropharyngeal infections in children: The experience of a pediatric hospital during the last decade - Correia, Isabel (2015)
Introduction: Retropharyngeal and lateropharyngeal infections frequently have an insidious presentation and are masked by previous treatments, being a diagnostic challenge. They are rare in the modern antibiotic age, but can cause potentially fatal complications.Material and methods: Retrospective study with analysis of data regarding epidemiology, etiology, clinical presentation, diagnosis, treatment and complications of children diagnosed with retro and lateropharyngeal infections in our pediatric hospital, from January 2001 to January 2012.Results: Twenty-three children were included, with ages between 3 months and 8 years, with an average age of 47 months (4 years). Thirteen (57%) had retropharyngeal infections, 2 (9%) had lateropharyngeal infections and 8 (35%) had both. The incidence was higher in 2010 (4 cases). Twelve (52%) were male and 11 (48%) were female. Odynophagia (57%), cervicalgia (26%) and refusal of oral intake (22%) were the most common symptoms. Fever (87%), torticollis and stiff neck (65%), neck mass (52%) and prostration (35%) were the most frequent physical findings. All (100%) patients had intravenous antibiotherapy. Medical treatment was instigated initially in 15 (65%) children. Medical treatment failure, with surgical drainage need, occurred in 5 (33%) of them. In one case, it was necessary to perform a second surgical drainage. Surgical treatment was initially proposed to 8 (35%) children, during the first 24 hours. This treatment had no failures (0%), and a second surgery was not required. However, in one child, a new abscess appeared in another location, that had to be drained. Two (9%) children had complications: mediastinitis, jugular vein thrombosis and Claude Bernard Horner syndrome.Conclusions: Presentation symptoms of retro and lateropharyngeal infections in pediatric population are varied, and their diagnosis require a high index of suspicion. Correct and timely treatment is essential for a favorable prognosis. The optimal management in patients without imminent airway obstruction is a subject of debate, particularly the choice between first line medical or surgical treatment. It is, therefore, essential more research in this topic, in order to optimize outcomes.